An Overview On Drug Regulatory Agencies: Europe And India - Patel, Bhoomi (International Journal of Pharmaceutical & Biological Archive, 2011)
Regulatory affairs in pharmaceutical industry aim at the protection of human health. People and government spent money on drugs because of the role they can play in saving lives, restoring health, preventing diseases and stopping epidemics. But, in order to do so, drug must be safe, effective and of good quality. Since the purpose of drug is to diagnose, prevent or treat diseases or ailments in humans, they are products intimately linked with the advances in research and regulation. The pharmaceutical industry, while pursuing an international market, is obliged to comply with national regulations. So, in this review article, an overview of few drug regulatory agencies of two countries: Europe and India is covered.